PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV DI MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Hikmah; Dede Indra Setiabudi; Iis Humaeroh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research examines the role of teachers in increasing students' learning motivation in Indonesian language subjects in class IV of Madrasah Ibtidaiyah Ma'had Al-Zaytun. Teachers at MI Ma'had Al-Zaytun participate actively not only in class, but also in the dormitory, so their role greatly influences student development. The statements that want to be answered through this research are 1) Describe the role of teachers in increasing learning motivation in class IV Indonesian language subjects at Madrasah Ibtidaiyah Ma'had Al-Zaytun, 2) To find out what are the supporting and inhibiting factors in increasing learning motivation in students. class IV Indonesian language lessons at Madrasah Ibtidaiyah Ma'had Al-Zaytun. This type of research is qualitative descriptive research. Data collection techniques are observation, interviews and documentation and the validity of the data is tested using triangulation techniques. The results of this research show that the teacher's role is very significant in creating a conducive learning atmosphere through various methods such as lectures, discussions and games. Teachers also provide special guidance to students who have difficulty understanding vocabulary and reading and writing skills. Effective teaching techniques, such as dictating and providing storybooks, are used to improve students' abilities. Motivation to learn is influenced by teacher support, peer interaction, and a good learning environment. The main supporting factors are support from teachers, room teachers, peers, and the home environment. However, some students still feel embarrassed and lose interest because they are not yet fluent in Indonesian. This research emphasizes the important role of teachers in increasing student motivation and academic achievement.